NEW CORRELATION TO ESTIMATE WELL RESERVES WITH DECLINE CURVE ANALYSIS AND BASED ON PRMS 2007 CLASSIFICATION - SUHARSONO (NIM : 22211020), ADITYA
Petroleum Resource Management System 2007 explained that reserves are categorized based on its status into Proved Developed and Proved undeveloped. Proved developed reserves category can be estimated using decline curve analysis / DCA, based on production data. While proved undeveloped reserve category (PUNDR) can generally be estimated by reservoir simulation. This study conducted at the reserve PUNDR production forecasts using the principle of equality of DCA. Analyses were performed using synthetic models assuming permeability and reservoir driving mechanism as a parameter that affects the rate of decline in production. After doing the analysis, plot parameters to the decline in the rate of production, and validation of field data, generate equations to predict decline rate based on the type of reservoir driving mechanism. The study produced the equation which has the general equation 𝐷𝑒 = 𝑦 𝑎 𝑚. The equation will be used to forecast production wells using a decline curve analysis equation.